Faktor Penerapan SMKK Pembangunan Gedung Sentra IKM Minyak Atsiri di Kecamatan Lunang - Rita, Eva; Saputra, Lariccia; Carlo, Nasfryzal; Jumas, Dwifitra Y.; Utama, Lusi (Universitas Batanghari Jambi, 2025)
The construction services industry is one of the industrial sectors that has a fairly high risk of work accidents. This occurs due to unsafe work actions and conditions, including weak implementation of the Construction Safety Management System (SMKK). Based on the results of field investigations on the construction project for the Essential Oil IKM Center Building in Lunang District, it shows that there are violations of the implementation of the SMKK. This research aims to (1) identify the factors that influence the implementation of SMKK, (2) analyze the factors that most dominantly influence the implementation of SMKK, and (3) provide solutions. This research is quantitative research involving 82 respondents from project owners, implementing contractors, and supervising consultants. Data collection was carried out through distributing questionnaires and data processing was carried out using Principal Component Analysis factor analysis using SPSS. Research findings (1) identified 6 (six) factors with 52 variables that influence the implementation of the SMKK, (2) the results of the analysis of the 6 (six) identified factors that influence the implementation of the SMKK, there are 5 (five) new factors that were formed which 4 (four) factors of which have the most dominant influence on the implementation of SMKK because they have a factor loading ≥ 0.65, and (3) identified solutions include: providing routine training on work safety procedures, activating Safety Morning Talk or Toolbox Meetings, monitoring the implementation of SMKK regularly strictly, as well as providing input or recommendations to the Pesisir Selatan Regency Regional Government Construction Services Development Team.